Preliminary Design for near Real-Time GPS Meteorology over Peninsular Malaysia (G-MeM) - Yusuf Drisu Opaluwa; Tajul Ariffin Musa; Abdullah Hisam Omar; Mustafa Din Subari; Lazarus Mustapha Ojigi (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
This paper presents a conceptual approach for near real time Global Positioning System (GPS) meteorology in Malaysia using combined space- and ground-based GPS observations. Data from a single GPS station is utilised to derive wet refractivities for comparison with radio occultation (RO). This study shows that the wet refractivities from the ground-based GPS present similar patterns and better correlation with the radiosonde data than that from the space-based GPS RO data at altitudes between 0 - 5 km. Similarly, the wet refractivities derived from RO are more highly correlated with the radiosonde data than the ground-based GPS at altitudes above 5 km. The residual Nw vary from -9.25 - 21.136 N-unit at 00 h UTC for the ground-based GPS while for the GPS RO, it is -19 - 9.259 N-unit at 00 h UTC.